2021
DOI: 10.1186/s12891-021-04878-2
|View full text |Cite
|
Sign up to set email alerts
|

Cement augmentation of the proximal femoral nail antirotation for the treatment of two intertrochanteric fractures - a comparative finite element study

Abstract: Background There are concerns regarding initial stability and cutout effect in proximal femoral nail antirotation (PFNA) treating intertrochanteric fractures. No study have used finite element analysis (FEA) to investigate the biomechanics. This study aimed to compare the cutout effect, stress and displacement between stable (AO31-A1.3) and unstable (AO31-A2.2) intertrochanteric fractures treated by cement augmented PFNA. Methods Four femoral finit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…The PFNA surgical treatment method can complete the corresponding material design according to the specific force principle of the patient's hip joint, which is closer to the patient's negative gravity line, which promotes the patient's load force transmission, and the overall diameter of the main nail is relatively small. Therefore, the joint stability and anti-rotation resistance of the treatment are increased to a certain extent [ 12 , 13 ]. In PFNA, its force transmission is internal expansion and extrusion, so that the medial and lateral sides of the femur can bear the stress in a balanced manner.…”
Section: Discussionmentioning
confidence: 99%
“…The PFNA surgical treatment method can complete the corresponding material design according to the specific force principle of the patient's hip joint, which is closer to the patient's negative gravity line, which promotes the patient's load force transmission, and the overall diameter of the main nail is relatively small. Therefore, the joint stability and anti-rotation resistance of the treatment are increased to a certain extent [ 12 , 13 ]. In PFNA, its force transmission is internal expansion and extrusion, so that the medial and lateral sides of the femur can bear the stress in a balanced manner.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al’s (2017) [ 22 ] modeling has shown the presence of higher stresses at the nail border and the neck screw using different types of nails, which was confirmed during real-life orthopedic surgery by [ 23 ]. Higher stresses have been reported about the locking screw and the lower part of the nail, being greater in GNF than DHS [ 24 , 25 ]. As with the present findings, modest bone stress has been described at the implant level compared to the implant itself.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies ( Li et al, 2010 ; Khor et al, 2018 ), the femoral fracture was defined by detecting a failure strain that was initiated and propagated by element deletion as long as the strain of an element reaches the limit. The fracture analyses were performed by LS-DYNA (LSTC, Livermore, CA) software to investigate the biomechanical effect of the failure test ( Zheng et al, 2021 ). Material properties applied for fracture analysis are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Material properties applied for fracture analysis are shown in Table 1 . The density of cortical bone, cancellous, and Ti6Al–4V titanium was obtained from previous reports ( Dhanopia and Bhargava, 2017 ; Zheng et al, 2021 ). According to the equations between bone density (ρ), Young’s modulus (E), and yield stress (σ) ( Morgan and Keaveny, 2001 ; Duchemin et al, 2008 ), cortical and cancellous bone’s yield stress was calculated respectively.…”
Section: Methodsmentioning
confidence: 99%